Transcriptional regulation of the thymus master regulator Foxn1 - Kadouri, Noam; Givony, Tal; Nevo, Shir; Hey, Joschka; Ben Dor, Shifra; Damari, Golda; Dassa, Bareket; Dobes, Jan; Weichenhan, Dieter; Bähr, Marion; Paulsen, Michelle; Haffner-Krausz, Rebecca; et al. (Science immunology, 2022)
FOXN1 is a transcription factor critical for the development of both thymic epithelial cell (TEC) and hair follicle cell (HFC) compartments. However, mechanisms controlling its expression remain poorly understood. To address this question, we performed thorough analyses of the evolutionary conservation and chromatin status of the Foxn1 locus in different tissues and states and identified several putative cis-regulatory regions unique to TECs versus HFCs. Furthermore, experiments using genetically modified mice with specific deletions in the Foxn1 locus and additional bioinformatic analyses helped us identify key regions and transcription factors involved in either positive or negative regulation of Foxn1 in both TECs and HFCs. Specifically, we identified SIX1 and FOXN1 itself as key factors inducing Foxn1 expression in embryonic and neonatal TECs. Together, our data provide important mechanistic insights into the transcriptional regulation of the Foxn1 gene in TEC versus HFC and highlight the role of FOXN1 in its autoregulation.
Gesehen am 29.11.2022